1998
DOI: 10.1111/j.1399-6576.1998.tb05109.x
|View full text |Cite
|
Sign up to set email alerts
|

The palm print as a sensitive predictor of difficult laryngoscopy in diabetics

Abstract: We believe that in the diabetic population, the palm print index may be a sensitive marker of difficult intubation. It is possible that other airway evaluation indices would prove more sensitive, and have greater utility, in distinct populations as compared to when they are applied to all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…16 A recent editorial recommended that metformin be discontinued 48 hr before elective surgery. 13 Published correspondence following the recommendation revealed that there is no evidence supporting 48-hr abstinence. 17 A Cochrane review of 176 randomized controlled trials of metformin did not identify a single episode of lactic acidosis in over 35,000 patient-years of therapy.…”
Section: How Long Before Surgery Should the Patient Discontinue Metfomentioning
confidence: 99%
See 1 more Smart Citation
“…16 A recent editorial recommended that metformin be discontinued 48 hr before elective surgery. 13 Published correspondence following the recommendation revealed that there is no evidence supporting 48-hr abstinence. 17 A Cochrane review of 176 randomized controlled trials of metformin did not identify a single episode of lactic acidosis in over 35,000 patient-years of therapy.…”
Section: How Long Before Surgery Should the Patient Discontinue Metfomentioning
confidence: 99%
“…Stiffness of the fourth and fifth interphalangeal joints (the prayer sign) assessed using palm prints is a sensitive predictor of difficult intubation. 13 A retrospective review of 725 patients undergoing renal or pancreatic transplantation found diabetics were at a fourfold increased risk of minimally to moderately difficult intubation. 14 All were successfully intubated by conventional means.…”
Section: Is This Patient At Particular Risk Of Airway Problems?mentioning
confidence: 99%
“…Their study interestingly noted that diabetic patients with easy laryngoscopy (Cormack-Lehane laryngoscopic view grades 1 and 2) had a mean glycosylated hemoglobin (HbA1c) of 6.2 ± 1.3%, whereas those with difficult laryngoscopy (Cormack-Lehane laryngoscopic view grades 3 and 4) had a mean HbA1c of 8.7 ± 1.9%. Some reports show the efficacy of the palm print as a sensitive predictor of difficult laryngoscopy in diabetic patients [14,17]. In contrast, Erden et al [18] reported no relationship between the ''prayer sign'' (inability to approximate the palmar surfaces of the phalangeal joints despite maximum effort) and difficult laryngoscopy.…”
Section: Stiff-joint Syndromementioning
confidence: 93%
“…A palm print score from 0-3 based on the degree of visibility of phalangeal areas on a piece of paper has been assessed as a factor to predict difficult laryngoscopy. [4][5][6][7] Several studies have compared it to other common clinical airway indices such as the Modified Mallampati score, thyromental distance and degree of neck extension and have found it to be the most sensitive predictor of difficult laryngoscopy in diabetic patients with sensitivity ranging from 75-100%. 6 7 The palm print test when used in combination with other airway assessment indices may improve the predictability of difficult laryngoscopy.…”
Section: Discussionmentioning
confidence: 99%